Tv e segunda tela : uma análise do horário nobre no Twitter - Canatta, Fábio (2014)
This dissertation has as its theme the second screen experience, i.e. the audience s habit of watching television connected to the internet in a navigation oriented by the TV content. The overall objective is to analyze whether the practice of second screen reinforces the value of the schedule, the TV stream, the live programming, and especially the social bond among viewers. Twitter s trend topics during television prime time were adopted as the research object and integrate the corpus of this study. The material was explored based on the content analysis systematized by Bardin (1977). The theoretical framework has concepts of Wolton (1996), Fechine (2008), Cannito (2010), Jenkins (2008), Castells (2009), Bolaño (2007), Recuero (2009) and Prouxl and Shepatin (2012), among others. It was concluded that second screen offers the audience a more complex experience, intensifies the social bond which becomes no longer invisible and silent and reinforces the value of the broadcast programming.